Covid-19 in Malaysia : numbers at a glance as of 16th May 2021, 12pm - Malaysia, Kementerian Kesihatan (Kementerian Kesihatan Malaysia (KKM), 2022)
This item is made available on Ministry of Health Malaysia, Covid-19 homepage at http://covid-19.moh.gov.my/